1997
DOI: 10.1103/physrevlett.79.3210
|View full text |Cite
|
Sign up to set email alerts
|

Island Diffusion and Coarsening on Metal (100) Surfaces

Abstract: The diffusion and coarsening of two-dimensional homoepitaxial islands on Cu(100) and Ag(100) surfaces have been studied at room temperature with time-sequenced scanning tunneling microscopy. Quantitative analyses of the dependence of island diffusion coefficient D vs the island side length L, D~L 2a , yield noninteger scaling exponents which are consistent with island coalescence. Moreover, the near absence of island decay shows that the island diffusion occurs via mass transport along the island periphery. [S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
215
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(234 citation statements)
references
References 16 publications
16
215
3
Order By: Relevance
“…We therefore study the decay of small islands in an environment of large ones, a situation that differs from the work of Pai et al 9 The images were recorded using a tunneling current of 1.0 nA with the tip biased negatively by 0.10-…”
Section: ͓S0163-1829͑98͒50836-3͔mentioning
confidence: 99%
See 2 more Smart Citations
“…We therefore study the decay of small islands in an environment of large ones, a situation that differs from the work of Pai et al 9 The images were recorded using a tunneling current of 1.0 nA with the tip biased negatively by 0.10-…”
Section: ͓S0163-1829͑98͒50836-3͔mentioning
confidence: 99%
“…For the Cu͑100͒ and the Ag͑100͒ surface this random-walk-induced coalescence can be the prevailing mechanism in the coarsening process. [8][9][10] Until recently it was tacitly assumed that atom exchange between islands and steps on metal surfaces is mediated via adatoms on the terraces as the diffusing species. In a recent study of Ostwald ripening on Cu͑100͒ it was proposed that single atom vacancies rather than adatoms are responsible for the mass transport between the islands.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most important questions that still remains open is the role of island diffusion, since for mobile islands the aggregation rates in the RE approach depend explicitly on the diffusion coefficients D s of islands of different sizes s. Island diffusion on surfaces has been studied both theoretically [7,8,9] and experimentally [10,11,12,13,14,15,16]. While in the large island limit the size dependence of the island diffusion coefficients can be classified based on simple basic processes [17], for smaller islands D s depends on the geometric and energetic details of the underlying surface, and can be a complicated, non-monotonic function of s [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…4 Recent studies have shown that in metal-on-metal systems even large clusters can have significant mobility at moderate temperatures. 5 This is due to such mechanisms as evaporation-adsorption, terrace ͑or vacancy͒ diffusion, and single-atom diffusion along the periphery. 4,6 Smaller clusters can diffuse with more complicated mechanisms, however.…”
mentioning
confidence: 99%